Social networks and academic performance in students of Universidad de Huanuco - Escobedo Rivera, Froilán (2019)
Objective. To determine the influence of social networks on academic performance of the students of Universidad de Huanuco during the academic year of 2018. Methods. It was an observational, cross- sectional and prospective study, with a correlational design. The population was 12674 students, and the sample was 373 students from Universidad de Huanuco. A questionnaire was used in data collection. For the inferential analysis, the Spearman’s Rho Correlation Test was used. Results. It was evidenced that 55.5 % (207/373) presented good academic performance, and 63 % (235/373) showed high use of social networks. Likewise, social networks significantly influence academic performance of students, with p <= 0.000. Academic performance is significantly influenced by social networks in the dimensions of common interests (p <= 0.000), type of information shared (p <= 0.000), communication benefits (p<= 0.002), and virtual communication (p <= 0.000). Conclusions. Social networks influence academic performance of the students of Universidad de Huanuco.